2020
DOI: 10.1109/access.2020.2984481
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations of Cavitation Phenomena Inside the Pilot Stage of the Deflector Jet Servo-Valve

Abstract: Two-stage electrohydraulic servo-valves play an important role in the most modern hydraulic servo control systems for fight wing controls, manufacturing robots, and many engineering applications. The existence of cavitation inside the pilot stage is one of the root causes of self-excited noise, cavitation erosion, system jam, and frequent failures of electrohydraulic servo-valves. Thus, experimental and numerical investigations of the flow field and cavitation phenomena inside the pilot stage of deflector jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Another issue concerned with two-stage servovalves is the complexity of the torque motor, which is made up of many sensitive mechanical and electrical parts, such as the flexure tube, being manufactured very accurately in order to achieve the required stiffness. The pilot stages of two-stage servovalves are also subject to intense cavitation, as shown by very interesting research studies [8][9][10][11], which also highlight that commercially available pilot stages are not optimized geometries [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Another issue concerned with two-stage servovalves is the complexity of the torque motor, which is made up of many sensitive mechanical and electrical parts, such as the flexure tube, being manufactured very accurately in order to achieve the required stiffness. The pilot stages of two-stage servovalves are also subject to intense cavitation, as shown by very interesting research studies [8][9][10][11], which also highlight that commercially available pilot stages are not optimized geometries [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Through understanding the key technology of jet pipe servo valves, it is found that there are many kinds of jet pipe servo valve. These mainly include rotary jet pipe servo valves, jet pipe valves, integrated jet pipe valves, slide valve end inclined jet pipe valves and middle jet pipe valves [7][8][9][10][11][12][13][14][15][16][17][18]. To verify the adaptability of jet pipe valves in aircraft braking systems, Yang [19] and Zhao [20] compared the performance indexes of nozzle flapper valves and jet pipe valves, and proposed that the key technical indexes of jet pipe valves meet the performance requirements of nozzle flapper valves.…”
Section: Introductionmentioning
confidence: 99%
“…However, electrohydraulic servovalve failure is common in airborne control systems and threatens control performance and even flight safety seriously. For example, a servovalve fault may exhibit spool oscillation, squeal noise, motion catching, etc., which can make the performance of the control system worse and can have catastrophic consequences [ 3 , 4 , 5 ]. Much work has been done on failure diagnosis and on reliability improvements for servovalves.…”
Section: Introductionmentioning
confidence: 99%